Ribosomal protein S7 from Escherichia coli uses the same determinants to bind 16S ribosomal RNA and its messenger RNA - Robert, Francis (Oxford University Press, 2001)
Ribosomal protein S7 from Escherichia coli binds to the lower half of the 3′ major domain of 16S rRNA and initiates its folding. It also binds to its own mRNA, the str mRNA, and represses its translation. Using filter binding assays, we show in this study that the same mutations that interfere with S7 binding to 16S rRNA also weaken its affinity for its mRNA. This suggests that the same protein regions are responsible for mRNA and rRNA binding affinities, and that S7 recognizes identical sequence elements within the two RNA targets, although they have dissimilar secondary structures. Overexpression of S7 is known to inhibit bacterial growth. This phenotypic growth defect was relieved in cells overexpressing S7 mutants that bind poorly the str mRNA, confirming that growth impairment is controlled by the binding of S7 to its mRNA. Interestingly, a mutant with a short deletion at the C-terminus of S7 was more detrimental to cell growth than wild-type S7. This suggests that the C-terminal portion of S7 plays an important role in ribosome function, which is perturbed by the deletion.